Trust and trusting practices during transition to higher education: Introducing a framework of habitual trust. Issue 2 (3rd April 2019) - Bormann, Inka; Thies, Barbara
ABSTRACT: Background : Transition to higher education (HE) confronts undergraduates with a variety of social and academic challenges. Research on how these challenges are dealt with often refers to a Bourdieusian perspective and links successful access to HE to the capital and habitus that students bring with them when adapting to unfamiliar institutional demands. Purpose : Although some studies regard trust (and perceptions of trustworthiness) as highly relevant for establishing a 'fit' between individual and institutional features, the notion of trust as a part of cultural capital for managing the transition to higher education is seldom considered. Our exploratory study aims to introduce and test out a framework for habitual trust and, thus, offer fresh insight into research on transition to HE. Sample : In order to investigate the role of trust for trusting practices, 28 undergraduates in two German Higher Education Institutions (HEI) were interviewed. Design and Method : Data were collected through episodic interviews. The transcriptions of these interviews were subject to typological qualitative content analyses. Results : The analysis of data identified three different types of students' trust and trusting levels, which varied in respect of academic or non-academic family background and affected students' trusting experiences at HEI. The three types of trust and trusting levels were: (i) proactive self-reliant trustors, (ii) adaptive and aspiring trustors, and (iii) resistant and alienated sceptics. Conclusions : Habitual trust can be considered as an important link between individual backgrounds and performance during the transition to HE. The results are discussed with a view to further research on the practicability of habitual trust as a feature that HEI can or should deal with.